2019
DOI: 10.3390/buildings9050109
|View full text |Cite
|
Sign up to set email alerts
|

Applying Level of Detail in a BIM-Based Project: An Overall Process for Lean Design Management

Abstract: Few construction companies apply the available lean tools and processes in an integrated manner when managing design. Additionally, lean design management tools and processes each have their own strengths and optimal phases in which they should be applied. Earlier approaches in lean design management have not explicitly included the level of detail of building information model (BIM) models in connection with planning methods. For example, the Last Planner System (LPS) uses collaborative social methods to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Moreover, integrating the design information and material flows into the rhythm of production was found to be critical for flow. Uusitalo et al (2019) have proposed a model to integrate levelof-design-based design management process with takt production, as aligning the design in parallel with takt time and takt areas would enable better flow in production, particularly during the ramp-up phase. In addition, just-in-time (JIT) material delivery matching the pace of work tasks was suggested as a significant enabler of flow; Tetik et al (2019) have suggested that centralized logistics control with JIT material delivery could improve flow by decreasing inventory buffers and variability in material flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, integrating the design information and material flows into the rhythm of production was found to be critical for flow. Uusitalo et al (2019) have proposed a model to integrate levelof-design-based design management process with takt production, as aligning the design in parallel with takt time and takt areas would enable better flow in production, particularly during the ramp-up phase. In addition, just-in-time (JIT) material delivery matching the pace of work tasks was suggested as a significant enabler of flow; Tetik et al (2019) have suggested that centralized logistics control with JIT material delivery could improve flow by decreasing inventory buffers and variability in material flow.…”
Section: Discussionmentioning
confidence: 99%
“…Releasing wagons in short cycles with more mature constraints reduces the amount of making-do, as more effort is expended to ensure the necessary requirements for work. The timing of the supporting flows, such as material flow (accompanied with adequate inventory buffers) and information flow, can and should be accurately planned to meet the preconditions of production, as the requirements for the flow are clearly determined in the takt plan (Uusitalo et al 2019). Thus, takt production enables the reduction of making-do (L7).…”
Section: Propositions On How Takt Production Affects Production Flowmentioning
confidence: 99%
“…In the as-is situation analysis, it was observed that design and design management were viewed as technical activities. Lean production and lean design management literature have recognized the need for a social conceptualization of design and design management [14,32,51]. However, Çıdık and Boyd [31] argued that no coherent social conceptualization had yet been developed.…”
Section: Summative Evaluation and Discussionmentioning
confidence: 99%
“…Kpamma and Adjei-Kumi (2011) argued that transferring the information in smaller batches would eliminate waste in the design process. Uusitalo et al (2019a) proposed a lean design management process that is applied to manage the LOD of design information and connect that information to location-based production in smaller batches, thus creating a pull to design information. Also, the proposed process utilizes collaborative methods, such as the Last Planner System (LPS) to determine the correct level and quantity of information and their milestones.…”
Section: Technical Design Processmentioning
confidence: 99%